Implementation of Tomato Juice in Hypertension with Readiness to Improve Health Management in Farmers: Case Report: Case Report - Khotijah; Istiqomah, Indriana Noor; Fibriansari, Rizeki Dwi; Azizah, Laili Nur (D'Nursing and Health Journal (DNHJ), 2025)
ABSTRACT Introduction: Hypertension is a major concern in global health due to its high incidence rate. To overcome this problem, there needs to be a strong desire to manage the problem of readiness to improve health management. Efforts that can be made by maintaining a lifestyle in this case are strengthened by providing foods high in potassium, one of which is tomato juice. The purpose of this final project report is to describe the implementation of tomato juice in hypertensive. Method: This report uses a case study design, with participants including 1 member of the farmer group who has hypertension, is 45 years old, has no complications, meets 80% of the symptoms, and has major signs of readiness to improve health management. The study was conducted on June 1-7, 2024 using interview, observation, and documentation techniques. Result: Tomato juice was given for 7 days with a dose of 1 time a day, after meals. The results of the case study showed a decrease in systolic blood pressure of 5.3 mmHg and diastolic blood pressure of 4.8 mmHg and the evaluation criteria for readiness to improve health management increased with participants being able to take action to reduce risk factors, implementing care programs, fulfilling daily activities, not experiencing difficulties in implementing health programs and receiving family support.   Conclusion: Providing tomato juice can be educational material for farmer groups and health management in the community can improve healthy eating patterns by providing tomato juice to control blood pressure.